Monitoring agricultural productivity for sustainable production and R&D planning - David Laborde Debucquet; Valeria Pi\~neiro (Kiel Institute for the World Economy (IfW), 2018)
Argentina's G20 presidency has emphasized the needs to improve soil management and increase agricultural productivity in a sustainable way to achieve an inclusive and resilient food future. While increases in agricultural productivity improve economic welfare and can help address food security problems by benefiting both consumers and producers simultaneously, it has to address the depletion of scarce natural resources. In the context of changing climate, achieving sustainable and resilient agricultural production is a major corner stone in both adaptation and mitigation strategies. The global community needs to have the proper tools to monitor sustainable agricultural productivity gains, identifying countries and sectors lagging behind, and committing R&D efforts accordingly to the challenges ahead. As such, it is suggested that 1) an international consortium should monitor Agricultural Total Factor Productivity to provide international comparisons and track performance over time; 2) the G20 should acknowledge and address the issue of sustainable productivity measurement, and; 3) support more in depth research on the relation between Agricultural TFP and Agricultural R&D.
Keywords: O13; O19; O33; Q16; Q18; 330; agricultural productivity; total factor productivity; TFP measurement; agricultural R&D; sustainable TFP; technological change